The Composite Assessment of River Performance viewed from Function, Structure, Public Participation and Government Regulation - Putri Pamudya Wardhani; Sobriyah Sobriyah; Cahyono Ikhsan (Institut Teknologi Sepuluh Nopember, 2017)
River performance is a quantitative representation showing fairly good, requiring maintenance- or damaged conditions. The assessment is conducted to implement the maintenance with appropriate management. It is the manifestation of government, stakeholders, and community’s anticipation to conduct repairing and maintenance before the damage occurring. The criterion of assessment is expressed in percentage. The case study in Pepe Baru River of Surakarta was conducted by designing the assessment of condition viewed from function, structure, public participation, and government regulation aspects. Indicator weighing was conducted using ANP (Analytic Network Process) method with Super Decision Beta software. The assessment of these components resulted in field weight. The assessment of function using Hec-Ras software, Structure aspect with visual observation, Public participation level was conducted using questionnaire distributed to the society with Guttman, Linkert scale method, and assessment according to government regulation. From the result of analysis, it could be found the indicator weight and field weight, so that the assessment of river performance was obtained. The result of performance assessment with 80%-100% score was categorized into good, 50%-79% into fair, and 0%-45% into poor. Considering the result of analysis on the performance analysis, it could be found the score of 74% indicating fair condition and the maintenance was required to improve the performance.